Mitigative Effect of Erythromycin on PMMA Challenged Preosteoblastic MC3T3-E1 Cells - Yi Shen; Weili Wang; Xiaomiao Li; David C. Markel; Weiping Ren (The Scientific World Journal)
Background. Aseptic loosening (AL) is a major complication of total joint replacement. Recent approaches to limiting AL have focused on inhibiting periprosthetic inflammation and osteoclastogenesis. Questions/Purposes. The purpose of this study was to determine the effects of erythromycin (EM) on polymethylmethacrylate (PMMA) particle-challenged MC3T3 osteoblast precursor cells. Methods. MC3T3 cells were pretreated with EM (0–10 μg/mL) and then stimulated with PMMA (1 mg/mL). Cell viability was evaluated by both a lactate dehydrogenase (LDH) release assay and cell counts. Cell differentiation was determined by activity of alkaline phosphatase (ALP). Gene expression was measured via real-time quantitative RT-PCR. Results. We found that exposure to PMMA particles reduced cellular viability and osteogenetic potential in MC3T3 cell line. EM treatment mitigated the effects of PMMA particles on the proliferation, viability and differentiation of MC3T3 cells. PMMA decreased the gene expression of Runx2, osterix and osteocalcin, which can be partially restored by EM treatment. Furthermore, EM suppressed PMMA- induced increase of NF-κB gene expression. Conclusions. These data demonstrate that EM mitigates the effects of PMMA on MC3T3 cell viability and differentiation, in part through downregulation of NF-κB pathway. EM appeared to represent an anabolic agent on MC3T3 cells challenged with PMMA particles.